2007
DOI: 10.2752/089279307x224818
|View full text |Cite
|
Sign up to set email alerts
|

Italian Youths' Attitudes toward, and Concern for, Animals

Abstract: This is the first comprehensive study of Italian youths'(9-18 years of age) attitudes and behaviors toward animals. Various aspects of child-animal relationships were analyzed, including pet ownership, pet attachment, pet loss, worries about pet, animal abuse (both perpetrated and witnessed), fears of animals, animals as a source of comfort, feelings toward road kill, and attitudes toward hunting, the use of furs and leather clothes, zoos, and the use of animals in circuses. Pupils from 12 schools anonymously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 30 publications
6
31
0
Order By: Relevance
“…Th e dislike of snakes seems to be a cross-cultural universal, since they rank lowest on the preference scale in reports from other countries (Africa: Kaltenborn et al, 2006;USA: Kellert & Westerveld, 1983; the Netherlands: Arrindell, 2000; Italy: Pagani, Robustelli, & Ascione, 2007;Spain: Martín-López, Montes, & Benayas, 2007). Th e present study failed to reveal signifi cant differences in the Negativistic dimension between Turkish and Slovakian students, supporting the universality of fear of snakes.…”
Section: Th E Eff Ect Of Countrymentioning
confidence: 92%
See 2 more Smart Citations
“…Th e dislike of snakes seems to be a cross-cultural universal, since they rank lowest on the preference scale in reports from other countries (Africa: Kaltenborn et al, 2006;USA: Kellert & Westerveld, 1983; the Netherlands: Arrindell, 2000; Italy: Pagani, Robustelli, & Ascione, 2007;Spain: Martín-López, Montes, & Benayas, 2007). Th e present study failed to reveal signifi cant differences in the Negativistic dimension between Turkish and Slovakian students, supporting the universality of fear of snakes.…”
Section: Th E Eff Ect Of Countrymentioning
confidence: 92%
“…Th e attitudes in Bjerke, Østdahl, and Kleiven's (2003) research were examined just in terms of participants' sympathies, leaving other dimensions of their attitudes (see, for example, Kellert, 1985) unexplored. Pagani, Robustelli, and Ascione (2007) found only a weak association between pet guardianship and empathic attitudes toward animals. Although these authors found that snakes were common objects of irrational fears on the part of Italian pupils, they did not examine the attitudes of pet caretakers toward snakes or less popular animals in general.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition to the avenues for future research noted above, further research needs to examine acceptable and unacceptable animal abuse in Bahamian society (this type of study could be based on Pagani, Robustelli, and Ascione, 2007) as well as how animals are portrayed and discussed in schools and homes.…”
Section: Resultsmentioning
confidence: 99%
“…The most well-known group was mammals. The reasons could be students' greater affection for mammals (Torkar, Kubiatko, & Bajd, 2012;Prokop & Tunnicliffe, 2010), more frequent contact with them (Pagani, Robustelli, & Ascione, 2007), mammals' charismatic nature (Torkar, Praprotnik, & Bajd, 2007;Barney et al 2005), or some other factor.…”
Section: Discussionmentioning
confidence: 99%